Comparative Analysis of Digital Literacy Effects on Cybercrime Awareness: Evidence from Generations Y and Z - Subagio, Aris; Syalevi, Rahmad; Jaya, Suhendra Saputra (KALBISOCIO Jurnal Bisnis dan Komunikasi, 2025)
This study aims to examine the influence of digital literacy and its dimensions - technical, cognitive, and social-emotional - on cybercrime awareness among university students, with a comparison between Generation Y and Generation Z. Adopting a quantitative approach, data were collected from 108 respondents through an online questionnaire using purposive sampling. Regression analysis revealed that all dimensions of digital literacy significantly affect cybercrime awareness, with the technical dimension having the most substantial impact. The generational comparison revealed that digital literacy had a significant influence on Generation Z, but no significant effect on Generation Y. These findings underscore the importance of adopting a multidimensional and generation-responsive approach to developing digital literacy and enhancing cybersecurity awareness.